Pengaruh Kepemimpinan Transformasional terhadap Kinerja Instruktur PT. United Tractors Tbk. Jakarta - Nugroho, Arif; Fauzobihi, Fauzobihi; Anggraini, Dian (Jurnal Ilmiah Mandala Education (JIME), 2022)
The purpose of the study was to determine the effect of transformational leadership on the performance of instructors at PT. United Tractors Tbk. Jakarta. Research methods with quantitative methods with data collection by means of a questionnaire. The population is 32 people from the sample of 32 people which means the type of sampling used is saturated sampling. This research was conducted by distributing questionnaires to instructors of PT. United Tractors Tbk. Jakarta. The analytical technique used in this study is a simple linear regression analysis technique. Based on the results of this study it can be concluded that the transformational leadership of PT. United Tractors Tbk. Jakarta is in the good category. Based on the results of the coefficient of determination that transformational leadership has a significant influence on employee performance by 26.5% and the remaining 73.5% which is influenced by other variables. The T test shows that the transformational leadership style has a significant influence on employee performance.